Isolation, structural elucidation, and immunoregulation properties of an arabinofuranan from the rinds of Garcinia mangostana. (15th October 2020) - Zhang, Shaojie; Li, Zhengguo; Wang, Xuelian; An, Lijun; Bao, Jiahe; Zhang, Jie; Cui, Jianlin; Li, Yuhao; Jin, Da-Qing; Tuerhong, Muhetaer; Abudukeremu, Munira; Ohizumi, Yasushi; et al.
Graphical abstract: Highlights: An arabinofuranan (GMP90-1) was first isolated from the rinds of G. mangostana . GMP90-1 was composed of arabinose, galactose, and rhamnose. GMP90-1 presented a rigid rod structure rather than a triple-helical structure. GMP90-1 stimulated RAW264.7 cells to produce TNF- α, IL-6, IL-1 β, and NO. The immunoenhancing activity of GMP90-1 was confirmed by an in vivo zebrafish model. Abstract: In our search for bioactive polysaccharides as immunomodulatory agents, an arabinofuranan (GMP90-1) was purified and characterized from the rinds of Garcinia mangostana L. GMP90-1 (absolute molecular weight: 5.30 × 10 3 g/mol) was found to be composed of arabinose, galactose, and rhamnose. The backbone of GMP90-1 was determined as (1→5)-linked α -l -Ara f, (1→2, 3, 5)-linked α -l -Ara f, (1→3, 5)-linked α -l -Ara f, (1→6)-linked β -d -Gal p, and (1→2)-linked α -l -Rha p . Conformational analysis revealed GMP90-1 to exist as a rigid rod structure in sodium chloride solution. To explore its potential as immunomodulatory agents, an in vitro cell screening was performed and GMP90-1 was found to significantly enhance the phagocytic uptake of neutral red and improve the secreted level of nitric oxide (NO), interleukin (IL)-6, IL-1 β, and tumor necrosis factor- α (TNF- α ) of macrophages. Furthermore, the cellular immunomodulatory activities were confirmed by the in vivo zebrafish experiment, which suggested that GMP90-1 with immunomodulatory effects could be considered as a potential immunomodulatory for immune diseases.